Government Versus Lex Sportiva: Government Authority in Accelerating the Development of National Football - Tri Nurhidayat; Dicky Eko Prasetio (Indonesian Journal of Administrative Law and Local Government, 2026)
This research aims to analyze the government's authority in accelerating the development of national football and its alignment with the transnational principle of lex sportiva, which emphasizes the independence and autonomy of sports organizations. This issue is important because the policy for accelerating the development of national football, regulated by Presidential Instruction Number 3 of 2019 and the Regulation of the Coordinating Minister for Human Development and Culture Number 1 of 2020, creates a potential normative conflict between the authority of the government as the organizer of governance and the authority of the All-Indonesian Football Association (PSSI) as the national football governing body. This research uses the normative legal research method with a regulatory approach and a conceptual approach. The research results show that the government has the authority to play a role in the development of football as a manifestation of the welfare state thru policy formulation, budget allocation, infrastructure development, human resource development, and law enforcement. However, the regulations in Presidential Instruction Number 3 of 2019 and Coordinating Minister for Human Development and Culture Regulation Number 1 of 2020 indicate a tendency to take over the strategic functions of the federation thru top-down coordination and control mechanisms, which potentially contradict the independence and autonomy aspects of sports organizations that are the foundation of the lex sportiva principle. This research argues that the development of national football should be carried out thru a balanced partnership model between the government and PSSI, with a clear division of authority between the public aspects that fall under the domain of the state and the technical aspects of sports that fall under the authority of the federation. The recommendation of this research is the need to establish a Presidential Regulation on the Acceleration of National Football Development, which provides legal certainty regarding the boundaries of authority between the government and PSSI, prevents overlapping authority, and ensures the harmonization between national law and lex sportiva in order to realize a professional, sustainable, and internationally competitive national football governance.